Traumatic neuromas of peripheral nerves: Diagnosis, management and future perspectives - Yang, Hu; Dong, Yanzhao; Wang, Zewei; Lai, Jingtian; Yao, Chenjun; Zhou, Haiying; Alhaskawi, Ahmad; Hasan Abdullah Ezzi, Sohaib; Kota, Vishnu Goutham; Hasan Abdulla Hasan Abdulla, Mohamed; Lu, Hui (Frontiers in Neurology, 2023)
Traumatic neuromas are infrequent in clinical settings but are prevalent following trauma or surgery. A traumatic neuroma is not a true malignancy, rather, it is a hyperplastic, reparative nerve reaction after injury and typically manifests as a nodular mass. The most common clinical manifestations include painful hypersensitivity and the presence of a trigger point that causes neuralgic pain, which could seriously decrease the living standards of patients. While various studies are conducted aiming to improve current diagnosis and management strategies via the induction of emerging imaging tools and surgical or conservative treatment. However, researchers and clinicians have yet to reach a consensus regarding traumatic neuromas. In this review, we aim to start with the possible underlying mechanisms of traumatic neuromas, elaborate on the diagnosis, treatment, and prevention schemes, and discuss the current experiment models and advances in research for the future management of traumatic neuromas.